Coenzyme Q0 From Antrodia cinnamomea Exhibits Drug-Resistant Bacteria Eradication and Keratinocyte Inflammation Mitigation to Ameliorate Infected Atopic Dermatitis in Mouse - Chou, Wei-Ling; Lee, Tzong-Huei; Huang, Tse-Hung; Wang, Pei-Wen; Chen, Ya-Ping; Chen, Chin-Chang; Chang, Zi-Yu; Fang, Jia-You; Yang, Shih-Chun (Frontiers in Pharmacology, 2019)
Atopic dermatitis (AD) is an inflammatory skin disease that is usually accompanied by Staphylococcus aureus infection due to cutaneous barrier-function damage. Benzenoid compounds from Antrodia cinnamomea are known to exhibit antibacterial and anti-inflammatory activities. This study sought to investigate the potential of benzenoids for treating bacteria-infected AD. The compounds were screened against methicillin-resistant S. aureus (MRSA). Coenzyme Q0 (CoQ0), a key ingredient in A. cinnamomea, showed the strongest MRSA growth inhibition. We further tested the inhibitory effect of CoQ0 on planktonic and biofilm MRSA. The work was also performed to explore the potential effectiveness of CoQ0 on AD using activated keratinocytes and in vivo experimental AD mice as the models. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of CoQ0 against MRSA were 7.81 μg/ml. CoQ0 was found to eradicate biofilm MRSA efficiently and reduce the biofilm thickness. CoQ0 killed MRSA by inhibiting DNA polymerase and topoisomerases. A proteomic assay showed that CoQ0 also reduced the ribosomal proteins. In the anti-inflammation study, CoQ0 was found to downregulate the expression of IL-6, CCL5, and CCL17 in HaCaT cells. CoQ0 at 0.5 μg/ml could recover the filaggrin decreased by HaCaT activation to the normal control. We established a bacteria-infected AD-like model in mice using ovalbumin (OVA) and topically applied MRSA. Topical CoQ0 delivery lessened the MRSA presence in the AD-like lesions by >90%. The erythema, barrier function, and epidermal thickness of the AD-like wounds were improved by CoQ0 through the reduction of IL-1β, IL-4, IL-6, IL-10, IFN-γ, and by neutrophil infiltration in the lesional skin. CoQ0 is therefore regarded as effective in mitigating AD symptoms associated with bacterial load.